2004
DOI: 10.1007/s10597-004-6125-5
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Recovery in People with Serious Mental Illnesses

Abstract: This study examines the relationship between objective and subjective measures of social support with recovery from serious mental illness; recovery has been described as both an outcome state and an ongoing process. One hundred and seventy six people with serious mental illness completed the Recovery Assessment Scale, a process measure of recovery that assessed, among other factors, personal confidence, goal orientation, and non-domination by symptoms. They also were administered the Brief Psychiatric Rating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
230
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(254 citation statements)
references
References 26 publications
16
230
2
6
Order By: Relevance
“…Previous psychiatric hospitalizations were significantly more common among inpatients than outpatients (4.3 ± 5.0 vs. 2.8 ± 2.7, p < 0.001). with serious mental illnesses with a larger overall network and greater network satisfaction have better rates of recovery 22,23 . The U.S. National Comorbidity study observed that most psychiatric disorders decline with age and with higher socioeconomic status 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous psychiatric hospitalizations were significantly more common among inpatients than outpatients (4.3 ± 5.0 vs. 2.8 ± 2.7, p < 0.001). with serious mental illnesses with a larger overall network and greater network satisfaction have better rates of recovery 22,23 . The U.S. National Comorbidity study observed that most psychiatric disorders decline with age and with higher socioeconomic status 24 .…”
Section: Resultsmentioning
confidence: 99%
“…The Recovery Assessment Scale (RAS; Corrigan et al, 1999 (Corrigan and Phelan, 2004) and leisure motivation (Lloyd et al, 2007) The Mental Health Recovery Measure (MHRM; Young and Ensing, 1999;Ralph, 2000).…”
Section: Participantsmentioning
confidence: 99%
“…Cobb 1976, Tolsdorf 1976, Hammer 1981, Winefield 1987, Sörensen and Dalgard 1988, Mitchell 1989, Nelson et al 1992, Biegel and Tracy 1994, Sörensen 1994, Albert et al 1998, Corrigan et al 2004, Cox 2006, Haber et al 2007, Dalgard and Sörensen 2009). Much of the research has been focused on definitions of social support and social networks, in addition to the identification of essential, active network factors such as size, quality, availability, density, reciprocity and utilization, how networks function and to what degree they facilitate service utilization and support recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the lack of conceptual clarity, research has documented that networks in general are more supportive than unsupportive (Nelson et al 1992), that social support acts as a moderator of life stress (Cobb 1976, Sörensen and Dalgard 1988, Williams et al 2004, Dalgard and Sörensen 2009, and that people with a reasonable overall network size and more network satisfaction are likely to report higher factors on the Recovery Assessment Scale (RAS) and a better quality of life (Corrigan et al 2004). Moreover, as self-reporting methods have demonstrated a high reliance (Glass andArnkoff 2000, Haber et al 2007), this article takes the clients' own descriptions of social support and recovery factors as valid information.…”
Section: Introductionmentioning
confidence: 99%